Education for a Civil Society - Osmanlić, Iljaz A.; Zukorlić, Mirsada S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Democracy presupposes an active participation of citizens who are conscious of their importance and responsible for their decisions. The contemporary democratic society can hardly function without a developed civic consciousness. There are no other, more reliable ways, to ensure such participation of people in the democratic processes than the system of education and upbringing. Therefore, democracy can be developed only by people who are convinced of its validity, who are familiar with its meaning and the modalities of its implementation. The main task of the educational system is to create average and responsible citizens. Without a doubt, the school does not possess an exclusive and monopolistic role in this matter. In this field, there is room for a variety of institutions that comprise a democratic society. Here, first of all, we consider political parties, syndicates, the church, as well as numerous non-governmental organizations, professional associations, and civil and democratic initiatives. Still, the role of the school and its educational system is indispensable. Education for life in a civil society must involve the adoption of its values. However, at the same time, reducing this adoption to unfounded coercion must be avoided. Certainly, such an action would only protect ignorance and hinder the freedom of choice, thus leading to more ignorance. This means that education for democracy must be democratic itself, it must be free, accepted without fear, and not imposed. Democratic decision-making depends on the reasonableness of conclusions in which everybody participates equally. Everyone's voice is respected but not worth the same, the decision is an expression of the will of the majority.
Keywords: education; value; citizen; democracy; freedom